PRODUKTIVITAS ALAT BERAT PADA PEMBANGUNAN PROYEK IRIGASI RENTANG LSS-07 DI RAMBATAN WETAN KABUPATEN INDRAMAYU - Mauluddin Barkah, Agung; Lia Lailla Nurjamilah (Universitas Majalengka, 2024)
The selection of heavy equipment affects the efficiency and profitability of construction work. The level of effectiveness of heavy equipment is assessed based on the productivity of the equipment. Productivity is the result of dividing output by input. The selection of heavy equipment is something important and must be considered so that its use is efficient and effective because it will affect the productivity of the machine. In the Rentang irrigation network construction project, there are several jobs that use heavy equipment such as piling and excavation work. The heavy equipment chosen must be right so that the project or work runs smoothly. The purpose of this study was to determine the productivity of heavy equipment, volume, number of heavy equipment and the time and cost of implementing heavy equipment. This study is limited to the problem of heavy equipment productivity, volume and time and cost of using heavy equipment. The heavy equipment used in the Rentang irrigation construction in Rambatan Wetan, Indramayu Regency is the PC 200 Excavator, the Sany SY215C Mini Excavator, and the Dump Truck. The productivity of the literature excavation excavator is 344 m3/hour, while the field data excavation is 377.68 m3/hour, the literature excavation dump truck according to the location of the dump truck work in Rambatan Wetan Village, Sindang District is 133.64 m3/hour.